Signifikansi Aspek Kompetensi Pedagogik Guru terhadap Pembelajaran Bahasa Inggris pada Siswa Sekolah Menengah Kejuruan Pertanian - Widya Puji Astuti; Babang Robandi (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
This research aims to elaborate the harmony between the psychological aspects of teachers' pedagogical competence and the actual findings in the implementation of English language learning process at the Vocational High School level. This research used a qualitative descriptive method. The data collection technique used direct observation and the research subject was the English teachet at ATPH Class 3 of SMKN 1 Pacet Cianjur. The data analysis procedures in this research were data analysis, data reduction, final interpretation, and verification. The results of the research showed that: (1) The teacher's pedagogical competence in preparing the learning process carried out by teachers in the ATPH 3 class showed the significance in accordance with the teacher's competence. This can be seen from the overall learning preparation being carried out structurally. Starting from lesson plans, games implementation, student worksheets, students’ attendance sheet and other tools. (2) The teacher's pedagogical competence when learning process took place in the ATPH class 3 showed good significance because the teacher implemented learning apperception. There was a communicative flow that increased student class engagement. However, the relevance of English language learning materials with students' interest in learning was not yet visible. (3) The teacher's pedagogical competence when implementing the reflection was good and the significance of the elements of teacher's pedagogical competence represented in the learning process.